Evaluasi Vitamin B pada Biskuit Bayi Substitusi Campuran Tepung Labu Kuning (Cucurbita Moschata Durch) dan Tepung Wortel ( Daucus Carrota L) - Afin Regina Cahyani; Mazarina Devi; Soenar Soekopitojo (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2023)
Consumption of food with sufficient nutritional content is very important to achieve optimal growth and development in infants and toddlers. Vitamin B is a vitamin that functions for metabolism in general and the formation of chemicals that function in nerve cells. This causes B vitamins to have an important influence on brain function. The aim of this study was to analyze the B vitamin content of biscuits substituted with pumpkin flour (Cucurbita moschata Durch) and carrot flour (Daucus carrota L). The highest content of vitamin B1 (thiamine), vitamin B2 (riboflavin), vitamin B3 (niacin), vitamin B6 (pyridoxine), vitamin B5 (pantothenic) was highest in biscuits which were substituted for pumpkin and carrot flour by 30 percent. The more substitutions of pumpkin and carrot flour, the greater the levels of vitamin B complex in pumpkin and carrot biscuits. This is because pumpkin and carrots are rich in vitamin B complex. Konsumsi makanan dengan kandungan gizi yang cukup sangat penting untuk mencapai pertumbuhan dan perkembangan yang optimal pada bayi dan balita. Vitamin B adalah vitamin yang berfungsi untuk metabolisme secara umum dan pembentukan zat kimia yang berfungsi pada sel saraf. Ini menyebabkan vitamin B memiliki pengaruh penting pada fungsi otak Penelitian ini bertujuan menganalisis kandungan vitamin B produk berupa biskuit yang disubtitusi dengan tepung Labu Kuning (Cucurbita moschata Durch) dan tepung wortel (Daucus carrota L). Kandungan vitamin B1 (tiamin), vitamin B2 (riboflavin), vitamin B3(Niasin), vitamin B6 ( piridoksin), vitamin B5 (pantothenik) tertinggi pada biskuit yang disubsitusi tepung labu kuning dan wotel sebesar 30 persen. Semakin banyak subtitusi tepung labu kuning dan tepung wortel, semakin besar kadar vitamin B kompleks pada biskuit labu kuning dan wortel. Hal tersebut dikarenakan labu kuning dan wortel kaya akan vitamin B kompleks.